2007
DOI: 10.1021/jo702193g
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Addition to Iminium Ethers in the Preparation of Functionalized N-Alkyl Heterocycles

Abstract: Bicyclic iminium ethers can be synthesized by the reactions of ketones with hydroxyalkyl azides. These cationic species react with a variety of nucleophiles via two possible pathways. The initially formed, kinetic product arises from direct addition to the iminium carbon in the substrate. In some cases, the initial adduct reverts to the starting iminium ether and the ultimate product arises from nucleophilic displacement at the O-alkyl group to afford the terminally functionalized N-substituted amide. The beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
3
22
0
2
Order By: Relevance
“…The preference for product formation via one path over another is dependent upon several factors, including nucleophile size and the nature of the anion-stabilizing group 15. Since all of the reaction partners used in this study were larger than those previously shown to result in path a products, it is not surprising that we observed a preference for addition to the less hindered site (path b in Table 3).…”
Section: Resultsmentioning
confidence: 69%
“…The preference for product formation via one path over another is dependent upon several factors, including nucleophile size and the nature of the anion-stabilizing group 15. Since all of the reaction partners used in this study were larger than those previously shown to result in path a products, it is not surprising that we observed a preference for addition to the less hindered site (path b in Table 3).…”
Section: Resultsmentioning
confidence: 69%
“…Labeling experiments suggest that pathway (2) is the more likely. 28 Alternatively, the transient formation of a tetrahedral intermediate is required for the formation of lactone 18 (control experiments ruled out direct conversion of 17 to 18 under these strongly basic conditions). N -Protonation of the aminal (pK a ca.…”
Section: Reactions Of Hydroxyalkyl Azidesmentioning
confidence: 99%
“…28,29 Through the addition of nucleophiles in a solution of DMF at ambient temperature, a range of lactams bearing terminal functional groups including ethers, halides, azides, and sulfi des were readily prepared (Table 7.4 ). It was also found that mild reduction (NaBH 4 ) of iminium ethers to the tertiary amine was possible, whereas reduction of the corresponding lactams typically required LiAlH 4 or borane.…”
Section: Reactions Of Hydroxyalkyl Azidesmentioning
confidence: 99%
“…The reaction represents an alternative to Schmidt reaction using hydroxyalkyl azides. [22][23][24][25][26][27][28] Studies of halogen-induced oxidative rearrangements of N,O-ketals were performed using 1a as a test substrate. Compound 1a was readily prepared by the condensation of cyclobutanone with a commercially available amino alcohol, 2-amino-3-phenylpropan-1-ol.…”
mentioning
confidence: 99%
“…The iminium ether intermediate ii has ambident electrophilicity, and the C2 and C4 positions of the oxazoline ring can react with nucleophiles. [22][23][24][25][26][27][28][30][31][32][33] Methyl ether 3a′ is not produced, and therefore nucleophilic attack by MeOH on intermediate ii selectively occurs at the C2 position rather than the C4 position of the oxazoline ring, to give a possible intermediate iii, which affords alcohol 3a on aqueous work-up.…”
mentioning
confidence: 99%